It seems so simple, but I can't think of a formal way of doing it. I never did proofs, so this would be good practice. This was a question the prof asked for curious ones to answer for the next lecture (he may forget about it), and it is not important. This is what I got, but there is some conflict: If [tex]x^2=1[/tex] - [tex]x=\pm 1[/tex], than [tex](-1)^2=(-1)(-1)=1[/tex]. It does make some assumptions, but I can't see a way around it. I can also use the definition of multiply, which means that it is the sum of a number taken a stated number of times. Because of this, the stated amount of times is -1. Adding this would be like this -(-1)=0. If it were -2(-1)=2, than -(-2)=2. Something a little more complicated (-2)(-3)=6, than -(-2)-(-2)-(-2)=6. Can someone help me here? PS. I want to impress the class. j/k!